Nash equilibrium in a pay-as-bid electricity market: Part 1 – existence and characterization. (3rd June 2017) - Aussel, D.; Bendotti, P.; Pištěk, M.
Abstract : We consider a model of a pay-as-bid electricity market based on a multi-leader-common-follower approach where the producers as leaders are at the upper level and the regulator as a common follower is at the lower level. We fully characterize Nash equilibria for this model by describing necessary and sufficient conditions for their existence as well as providing explicit formulas of such equilibria in the market.